Maternal prepregnancy BMI and physical activity and type 1 diabetes in the offspring. Issue 7 (23rd July 2021) - Azeredo, Catarina Machado; Cortese, Marianna; Munger, Kassandra L.; Ascherio, Alberto
Abstract: Background: Previous studies showed conflicting results on the association between maternal prepregnancy body mass index (BMI) and type 1 diabetes in the offspring, and the role of maternal prepregnancy physical activity is unclear. We aimed to assess whether maternal prepregnancy BMI and physical activity predict type 1 diabetes in their offspring. Methods: Prospective study including women participating in the Nurses' Health Study II with follow‐up from 1989 to 2011. Women repeatedly reported their BMI and physical activity, from which prepregnancy exposures were derived; and retrospectively reported their BMI at age 18 and physical activity at ages 18–22, considered early adulthood exposure. We estimated risk ratios (RR) and 95% confidence intervals (95%CI) using generalized estimating equations, adjusted for covariates. Findings at p < 0.05 were considered statistically significant. Results: We identified 276 cases of type 1 diabetes among offspring ( n = 70, 168) with maternal prepregnancy information and 448 cases among offspring ( n = 111, 692) with maternal early adulthood information. Prepregnancy and early adulthood maternal BMI and physical activity were not associated with offspring type 1 diabetes. The RR comparing overweight to normal weight mothers was 1.08 (95%CI: 0.73–1.59) and comparing obese to normal weight was 0.94 (95%CI: 0.49–1.79, p ‐trend: 0.98). Comparing highest to lowest quartile of maternal physical activity the RR was 0.90 (95%CI: 0.61–1.32; p ‐trend: 0.73). Maternal type 2 diabetes was associated with an increased risk of type 1 diabetes in the offspring (RR = 1.87; 95%CI: 1.25–2.80). Conclusions: Our findings do not support a relationship between maternal prepregnancy BMI or physical activity and the risk of type 1 diabetes in the offspring.